Viral mechanisms of adipose dysfunction: lessons from HIV-1 Vpr - Agarwal, N (Adipocyte, 2014)
HIV-associated lipodystrophy is a heterogeneous, evolving condition associated with fundamental defects in adipose tissue differentiation, turnover and function. Although many antiretroviral drugs can affect adipose tissues adversely, clinical evidence suggests that factors associated with the virus per se could play a role. We have focused on the possibility that an HIV accessory protein, viral protein R (Vpr) could dysregulate metabolically critical transcription factors to cause the adipose dysfunction. In a recent study published in Science Translational Medicine, we utilized 2 animal models to show that Vpr, produced in tissues that sequester HIV after antiretroviral therapy, can act in a paracrine or endocrine fashion to disrupt adipocyte differentiation and function by inhibiting PPARγ target gene expression and activating glucocorticoid target gene expression. The phenotypic consequences included many features typical of the human syndrome, including accelerated lipolysis, increased macrophage infiltration in adipose tissue, diminished size of white adipose depots and hepatic steatosis. In this commentary, we summarize the background, results, and implications of these studies, and raise important questions for future investigation. More broadly, these studies suggest that chronic viral infections may be a causative factor in the pathogenesis of some forms of lipid metabolic disease, insulin resistance, and diabetes.